Pendidikan Lingkungan Berbasis Islam dan Aksi Bersih Pantai di Pantai Baru Seliper Ate, Sumbawa - Ovi Soviya; Lina Eta Safitri; Musmulyadin Musmulyadin (Transformasi Masyarakat : Jurnal Inovasi Sosial dan Pengabdian, 2026)
Environmental pollution in coastal areas continues to be a critical issue, particularly in regions with high tourism activity such as Pantai Baru Seliper Ate in Sumbawa. The increasing accumulation of plastic waste and the lack of environmental awareness among visitors and local communities highlight the need for educational and practical interventions. This community service program aimed to strengthen students’ understanding of environmental cleanliness through Islamic values and participatory actions. The method consisted of short religious-based environmental education, a collaborative beach-cleaning activity, and a reflective session designed to reinforce ecological and spiritual awareness. The results showed a significant increase in students’ knowledge of environmental ethics, Islamic principles related to cleanliness, and practical skills in waste identification and sorting. The program also succeeded in improving the physical condition of the beach and fostering collective responsibility among participants. These findings indicate that integrating environmental education with Islamic values and hands-on activities can effectively enhance environmental awareness and support sustainable behavior among young people.